Analysis of Vitamin Content in Tropical Fruits - Jumrah, Elfira (Hayyan Journal, 2024)
Fruits are pointed out as natural sources of antioxidants, playing protective roles against aging, and chronic and degenerative pathologies. In this review it is shown that virtually unknown edible tropical fruits present significantly higher antioxidant activity when compared to temperate fruits considered to be good sources of antioxidantsThe tropical fruits, namely, Psidium Guajava L, Mangifera Indica L, and Carica Papaya L, are tropical fruits that have many benefits for the human body. They are rich in vitamin C, with three times the amount found in oranges, ten times the quantity found in papaya, and thirty times that found in bananas. Papaya is one of the fruit commodities that can be used almost as much. Crystal guava is a tropical fruit that is known to contain a large amount of vitamin A, and can be consumed regularly as a good antioxidant. It has various health benefits, such as antioxidant properties, improving digestive health, helping to lose weight, relieving flu symptoms, maintaining eye health, and nourishing the skin. It is also known that mango is an important source of micronutrients, vitamins, and other phytochemicals. Mango is called mango plants originate from India. The fruit is rich in vitamins A, C, D, and E, and it is also rich in antioxidants. The content of vitamin C is also high. The antioxidant activity test of ethanolic extract from solanum family leaves using methanol is used to reduce inflammation and protect body cells from the effects of free radicals that have the potential to cause various diseases. Further research is needed to better know the content of vitamins and pharmaceutical science natural ingredients with the ultimate goal, fruits that can overcome various health problems.